PENGARUH PARTISIPASI ANGGARAN PADA SENJANGAN ANGGARAN DENGAN GROUP COHESIVENESS SEBAGAI VARIABEL MODERASI - Permata, Citra Mega; Wirasedana, I Wayan Pradnyantha (E-Jurnal Akuntansi; Vol 10 No 2 (2015), 2015)
Management participation on budgeting process of a company can lead to dysfunctional behavior, namely the tendency of managers to create budgetary slack. The purpose of this research is to examine the effect of budgetary participation on budgetary slack and to test the effect of group cohesiveness as a moderating variable on the relationship budgetary participation and budgetary slack. This study was conducted on 45 construction company in Denpasar with the method of data collection is using questionnaire techniques. Total population used was 135 respondents using purposive sampling and the analysis of technique that used is Moderated Regression Analysis. The final results indicate that there is a positive effect of budget participation on budgetary slack. This effect also was moderated by the negative direction by the variable group cohesiveness. Thus, it can be concluded that group cohesiveness is able to weaken the effect of budgetary participation on budgetary slack.
Keywords: budget participation, slack, group cohesiveness